Financial Crises and Financial Contagion in Japan - A. O. Ovcharov (Russian Japanology Review, 2023)
The article analyzes the features of the financial crises in Japan in the context of using theoretical and practical approaches to financial contagion. A brief overview is made with the identification of the causes, nature, and consequences in relation to the three significant financial crises observed in the period 1990– 2009. A strong impact on the Japanese economy was exerted by the banking crisis of 1997–2001, which became one of the most noticeable events of the “lost decade.” Its lessons allowed the Japanese government to overcome the global financial crisis of 2007–2009 with minimal losses, which negatively affected not so much the credit and stock markets as the real sector of the Japanese economy and its foreign trade. From a scientific standpoint, the spread of crises is productively considered from the standpoint of the theory and methodology of financial contagion. It is a process of transmission of negative shocks that can lead to the disruption of fundamental links between countries and markets, thereby contributing to the growth of crises and instability. The article shows that Japan can act as both a transmitter and a recipient of infection. Examples of studies that examine the channels and direction of financial contagion in Japan are given. An important feature has been identified, which is that the main channel for the transmission of shocks in a given country is trade relations, and not financial ones. Taking this circumstance into account explains the effectiveness of the policy of supporting the real sector of the economy pursued by the Japanese government during the global financial crisis of 2007–2009. In order to illustrate the methodology of financial contagion, the article conducted an empirical study of the country and cross-industry effects of infection in the Japanese economy during the COVID-19 period. A specific infection detection tool (statistical tests) and an extensive empirical base were used. As a result, the country effects were confirmed only partially – Japan was the recipient of the financial contagion that came from China, but weakly transferred it to other countries. Cross-industry infection spread more actively (it was recorded by more than half of the tests). At the same time, uneven transmission of shocks between sectors was detected; possible causes of high or low susceptibility to infection in different sectors were discussed.